Exploration in stop motion animation / Muhammad Hazwan Mohamad Rahim - Mohamad Rahim, Muhammad Hazwan (2019)
Stop-motion animation is one of many types of animation, which also happen to be the earliest form of animation in history. It has been a part of the great pantheon of filmmaking since its birth in the early twentieth century. But ever since computer-generated animation in the form of 2D animation and 3D animation emerged, it has started gaining less popularity to both viewers and the creators as it is seen as the start of the downfall of stop animation. To find out the reason behind this, this research intends to point out and investigate the stop-motion animation process. With this, the researcher explores the process of making stop-motion animation step-by-step to understand its nature and learn its flaw to get a grasp of the reason stop-motion animation is declining.